2009
DOI: 10.1109/led.2008.2009008
|View full text |Cite
|
Sign up to set email alerts
|

First Internal Spacers' Introduction in Record High $I_{\rm ON}/I_{\rm OFF}\ \hbox{TiN/HfO}_{2}$ Gate Multichannel MOSFET Satisfying Both High-Performance and Low Standby Power Requirements

Abstract: For the first time, internal spacers have been introduced in multichannel CMOSFET (MCFET) structures, featuring a decrease of the intrinsic CV /I delay by 39%. The process steps introduced for this new MCFET technological option are studied and optimized in order to achieve excellent I ON /I OFF characteristics (NMOS: 2.33 mA/μm at 27 pA/μm and PMOS: 1.52 mA/μm at 38 pA/μm). A gate capacitance C gg reduction of 32% is measured, thanks to S-parameter extraction. Moreover, a significant improvement of the analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Those stacked Si nanowires were fabricated by (i) growing SiGe/Si superlattices on SOI wafers, (ii) protecting those stacks with a hard mask (in the channel regions), (iii) etching those stacks down to the starting Si film of the SOI substrate in the S/D regions, (iv) laterally etching recesses in the SiGe layers of the resulting fin-like structures, (v) filling those recesses with SiN internal spacers prior to (vi) Si:P SEG. 22 Later in the process flow, the SiGe layers were etched selectively versus Si and the resulting voids filled with the conformal gate stack materials. The surface of these RSDs was smooth, and full selectivity versus SiO 2 (Buried OXyde) and SiN internal spacers was achieved, as illustrated by the Scanning Electron Microscopy images in Figure 5.…”
Section: Impact Of the Ph 3 Mass-flow On The Si:p Growth Kinetics And...mentioning
confidence: 99%
“…Those stacked Si nanowires were fabricated by (i) growing SiGe/Si superlattices on SOI wafers, (ii) protecting those stacks with a hard mask (in the channel regions), (iii) etching those stacks down to the starting Si film of the SOI substrate in the S/D regions, (iv) laterally etching recesses in the SiGe layers of the resulting fin-like structures, (v) filling those recesses with SiN internal spacers prior to (vi) Si:P SEG. 22 Later in the process flow, the SiGe layers were etched selectively versus Si and the resulting voids filled with the conformal gate stack materials. The surface of these RSDs was smooth, and full selectivity versus SiO 2 (Buried OXyde) and SiN internal spacers was achieved, as illustrated by the Scanning Electron Microscopy images in Figure 5.…”
Section: Impact Of the Ph 3 Mass-flow On The Si:p Growth Kinetics And...mentioning
confidence: 99%
“…Making the approximation e spacer = e high-K and L spacer = T ox in GAA, we found that C epi is roughly 40Â higher in GAA than in single gate FDSOI. Nevertheless, Bernard et al [36] proposes the introduction of internal spacers to decouple the gate and the S/D. Fig.…”
Section: Dynamic Performance Evaluationmentioning
confidence: 99%
“…Slight improvement is found by switching from GAA-bulk integration to GAA-SOI integration thanks to its lower junction capacitance. More interesting, the integration of internal spacers [36] allows the reduction of the coupling between the epitaxially raised S/D and the gate. C epi is thus almost the same for the GAA than for the FDSOI.…”
Section: Dynamic Performance Evaluationmentioning
confidence: 99%
“…Moreover, some parasitic capacitances are created by the 3D configuration of such GAA architectures. In (6), a strategy to reduce the parasitic capacitances was proposed. It consisted in introducing internal spacers between the gates and the source/drain before the source/drain epitaxy.…”
Section: Small Channel Width Controlmentioning
confidence: 99%
“…Nevertheless, aggressive sub-lithographic nanowires' diameters will limit the current drivability of such devices. 3 dimensional (3D) stacked channel architectures were thus proposed (4)(5)(6)(7)(8)(9), with a significant gain in current density per surface area.…”
Section: Introductionmentioning
confidence: 99%